2011
DOI: 10.1016/j.jpeds.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Circulating Platelet Counts and Ductus Arteriosus Patency after Indomethacin Treatment

Abstract: Objective To determine if low platelet counts are related to the incidence of patent ductus arteriosus (PDA) after indomethacin treatment in preterm human infants. Study design Multivariable logistic regression modeling was used for a cohort of 497 infants, who received indomethacin (within 15 hours of birth). Results Platelet counts were not related to the incidence of permanent closure following indomethacin constriction. There was a relationship between platelet counts and the initial degree of constric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 32 publications
3
61
5
Order By: Relevance
“…Therefore, rather than finding higher rates of PDA among infants with the lowest platelet counts, they found that the relationship between the incidence of PDA and platelet counts appeared to be primarily influenced by the high end of the platelet distribution curve. However, it should be noted that the study of Shah et al [11] is not comparable with our study and the above-mentioned studies since the closure of the DA was influenced by the use of prophylactic indomethacin.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, rather than finding higher rates of PDA among infants with the lowest platelet counts, they found that the relationship between the incidence of PDA and platelet counts appeared to be primarily influenced by the high end of the platelet distribution curve. However, it should be noted that the study of Shah et al [11] is not comparable with our study and the above-mentioned studies since the closure of the DA was influenced by the use of prophylactic indomethacin.…”
Section: Discussioncontrasting
confidence: 99%
“…Whether this is also the case in human infants remains controversial [8,9,10,11,12]. Our data show that in a cohort of preterm VLBW infants the median platelet count nadir and the rate of mild, moderate or severe thrombocytopenia - within the first 2 days of life - were not significantly associated with the presence of HSPDA on day 3.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…[14][15][16] Moreover, the complication is high and carries significant contraindications. [17][18][19][20][21][22] When drug fails or contraindicated, next option is surgery. But surgery carries significant mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%